Pengaruh Kualitas Pelayanan Terhadap Loyalitas Pengguna Tokopedia Melalui Kepuasan Pelanggan - Fitri Khoerunisa; Resista Vikaliana (Universitas Persada Indonesia YAI, 2022)
The purpose of this study is to determine the effect of service quality on loyalty throughcustomer satisfaction as an intervening variable. Furthermore, to apply these objectives, aquantitative approach method with linear regression analysis is used. The results also showthat customer satisfaction is able to mediate the relationship between the influence of servicequality on customer loyalty to Tokopedia users. This study proves that service quality has a directeffect on loyalty and can also have an indirect effect, namely from service quality tocustomer satisfaction (as an intervening variable) and then to loyalty